Environmental Protection In John Green's Looking For Alaska Novel (2005): An Ecological Approach - Astriyani, Fitria, Dr. Phil. Dewi Candraningrum, M.Ed (2016)
The major problem of this study is environmental protection. Someone who suddenly gets an environmental protection must experience big change in life. The objective of this study is to analyze this novel based on ecological approach. The writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is looking for Alaska novel by John Green. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the novel. The secondary data of the study are taken from any information related to the novel. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the major character is his environmental protection. It is proven by his friend that they have been great pranks. He is defined by the research for answers about life and death after a fatal car crash.